Fluid Intelligence Moderates the Link Between Psychopathy and Aggression Differently for Men and Women. Issue 5 (March 2022) - Thomson, Nicholas D.; Kevorkian, Salpi; Bozgunov, Kiril; Psederska, Elena; Aboutanos, Michel; Vasilev, Georgi; Vassileva, Jasmin
Research on sex differences in the association of psychopathy with fluid intelligence is limited, and it remains unknown if fluid intelligence plays a meaningful role in explaining the psychopathy–aggression link for men and women. The present study aimed to test for sex differences in the relation between the four-facet model of psychopathy and intelligence, and to assess whether fluid intelligence moderates the link between psychopathy and aggression. In a community sample of men ( n = 356) and women ( n = 196), we assessed psychopathy using the Psychopathy Checklist: Screening Version (PCL:SV), fluid intelligence using the Raven's Progressive Matrices, and types of aggression using the Aggression Questionnaire (AQ). Hierarchical regressions showed that the psychopathy lifestyle facet was negatively associated with intelligence and there were no sex differences. Our analyses for types of aggression revealed sex differences and similarities. For both men and women, total AQ scores were predicted by higher antisocial facet scores. Lower intelligence moderated the link between higher antisocial facet scores and aggression in men, but not for women. Physical aggression in women was associated with higher interpersonal, affective, and antisocial facet scores, whereas for men, it was only associated with higher antisocial facet scores. Verbal and indirect aggression were associated with higher intelligence in both men and women. For men only, higher antisocial facet scores were associated with verbal and indirect aggression. Higher intelligence moderated the link between the lifestyle facet and indirect aggression for women, whereas for men, it moderated the link between the affective facet and indirect aggression. This study further highlights sex differences in mechanisms of psychopathy-related aggression, which need to be considered in the development of violence interventions and risk assessment.